Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.21608/adjalexu.2019.57568
|View full text |Cite
|
Sign up to set email alerts
|

Remineralization Effect of Fluoride Varnish Containing Casein Phosphopeptide Amorphous Calcium Phosphate on Caries-Like Lesions in Primary Teeth (In Vitro Study)

Abstract: INTRODUCTION:Fluoride containing casein phosphopeptide amorphous calcium phosphate (CPP-ACP) varnishes are now available as (MI Varnish). It has an effect on the remineralization process of demineralized enamel, since it has the highest release of calcium and fluoride ions. OBJECTIVES:To study the remineralizing effect of fluoride varnish containing casein phosphopeptide amorphous calcium phosphate (MI varnish) on the remineralization of caries-like lesions in primary teeth compared to sodium fluoride varnish.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Various methods have been used to study remineralization of carious lesions, such as microradiography, polarized light microscopy, microhardness, mineral analysis of calcium phosphate phases, transmission and scanning electron microscopy [38] . One of the recent technique that are used to quantitatively measures the small changes in the mineral content is Energy Dispersive X-ray spectroscopy (EDX) [39] . EDX analysis of CESP has been conducted in order to evaluate the elemental composition of the material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods have been used to study remineralization of carious lesions, such as microradiography, polarized light microscopy, microhardness, mineral analysis of calcium phosphate phases, transmission and scanning electron microscopy [38] . One of the recent technique that are used to quantitatively measures the small changes in the mineral content is Energy Dispersive X-ray spectroscopy (EDX) [39] . EDX analysis of CESP has been conducted in order to evaluate the elemental composition of the material.…”
Section: Discussionmentioning
confidence: 99%
“…This explains the significant difference in mean Ca/P wt% and hardness of remineralized and demineralized enamel samples in our study [19] . The pH cycling protocol followed in the present study is of particular interest because it simulates in vivo high caries risk condition and simultaneously measures the net result of the inhibition of demineralization and the enhancement of remineralization [39] . In this model, the dynamic cycles of de-and re-mineralization are simulated by sequentially immersing enamel specimens in acidic (demineralizing) and supersaturated (remineralizing) buffer solutions.…”
Section: Discussionmentioning
confidence: 99%
“…This study agrees with the previous ones, as the NaF and F-ACP complex showed a good remineralizing efficacy ( Figure 4 and Figure 6 ). F varnishes contain 5% NaF (approximately 20 times the F concentration of traditional toothpastes), which aids in the formation of long-lasting intraoral fluoride reservoirs [ 43 ]. The prolonged release of remineralizing ions over time from the RA is required to optimize the probability of caries prevention, particularly in individuals at a high risk of caries [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one of the study’s limitations is that an in vitro protocol and the pH cycling model are unable to completely simulate the complex intraoral conditions leading to caries development, where the pH fluctuates frequently. The oral pH levels depend upon the individual’s eating habits, oral hygiene practices, fluoride usage, and the composition and the quality of saliva and plaque [ 43 ]. For this reason, further in vitro studies and especially clinical trials are needed to validate the promising outcome of this research and clinically evaluate the remineralization efficacy of RA [ 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the results of the current study revealed that the use of 5% sodium fluoride cannot increase the concentration of phosphate and calcium ions significantly of saliva. This may be because of the utilized fluoride paste in this study did not containing CPP-ACP that is available in other products such as MI Paste; which contain 2% CPP-ACP in addition to 5% sodium fluoride (20,21) . This agreed with the results of Hay and Thomson, (22) which reported that the utilization of CPP-ACP significantly decrease caries when compared with 0.05 NaF mouth washing between individuals with dry mouth.…”
Section: Discussionmentioning
confidence: 99%